ПОНЯТТЯ ТА ЗМІСТ ПРАВА НА БАТЬКІВСЬКЕ ВИХОВАННЯ - Маковецька, В.В. (SUPREMANCE OF LAW, 2018)
The article is devoted to the study of the right to parental care, namely its concept. It is concluded that the right to parenting corresponds to the duty of parents to bring up their children, which in turn is also the right of parents, because according to the law, they have the right to choose forms and methods of education, in addition to those that contradict the law, the moral principles of society. It is concluded that the right to parental education is a relative right, which is subject to absolute protection. As to the content of the right to parental upbringing, it is impossible to define it unambiguously, it is difficult to provide an exhaustive list of powers that constitute the contents of the right of the child to education, since they are, firstly, of an appraisal nature, and secondly, one authority may exclude another.